Preclinical investigations towards the first spacer gel application in prostate cancer treatment during particle therapy at HIT - Ruciński, Antoni Wojciech; Bauer, Julia; Campbell, Patrick; Brons, Stephan; Unholtz, Daniel; Habl, Gregor; Herfarth, Klaus; Debus, Jürgen; Bert, Christoph; Parodi, Katia; Jäkel, Oliver; Haberer, Thomas (Radiation oncology, 2013)
The application of spacer gel represents a promising approach to reliably spare the rectal frontal wall during particle therapy (IJROBP 76:1251-1258, 2010). In order to qualify the spacer gel for the clinical use in particle therapy, a variety of measurements were performed in order to ensure the biological compatibility of the gel, its physical stability during and after the irradiation, and a proper definition of the gel in terms of the Hounsfield Unit (HU) values for the treatment planning system. The potential for the use of the spacer gel for particle therapy monitoring with off-line Positron Emission Tomography (PET) was also investigated.